The Threat that Social Media Crimes Pose to International Law Principles - Alni, Zainab Ahmed; Futaih, Raad Fejer; Turki, Mohammed; Al-Musawi, Oudha Yousif Salman; Taran, Ganna (Journal of Ecohumanism, 2024)
Background: As the worldwide community becomes increasingly linked via digital platforms, the rise in social media crimes brings unprecedented problems to the global legal environment. Traditional international law frameworks were often based on physical limits and tangible contacts, rendering them less able to manage the virtual and borderless character of these new types of wrongdoing. Objective: This article aims to identify places where present legal conceptions may need to be revised or misaligned by illuminating the gaps and conflicts between social media-related crimes and international law principles. Methods: Using a qualitative review of landmark cases, international treaties, and conventions, this study examines the compatibility of international legal instruments with the distinctive features of crimes committed via social media platforms. Results: The results show that the complexities of social media crimes regularly call into question numerous significant concepts of international law, such as jurisdiction, sovereignty, and non-interference. Furthermore, the need for a global definition and identification of some cybercrimes exacerbates discrepancies and uncertainty in international legal responses. Conclusion: International legal frameworks must be reassessed and restructured to address social media crimes. This might lead to more effective and coordinated global cybersecurity solutions in the digital age.